Comparative Evaluation of Triphala and Ela Decoction With 0.2% Chlorhexidine as Mouthwash in the Treatment of Plaque-Induced Gingivitis and Halitosis: A Randomized Controlled Clinical Trial - Pratibha Mamgain MD (Ayur); Abhishek Kandwal MDS (Periodontology); Ravindra K. Mamgain MD (Ayur) (SAGE Publishing, 2017)
Present study evaluates efficacy of Trifala and Ela as plaque controlling agent and compares it with chlorhexidine. Aim. To evaluate Antigingivitis, Antiplaque and Antihalitosis effect of Triphala and Ela decoction. A randomized sample of 60 patients with plaque induced gingivitis was enrolled and equally divided into two groups group A and group B. Group A was given Trifala and Ela decoction and Group B Chlorehexidine mouthwash for 21 days twice daily. Gingival inflammation index, plaque index and Organoleptic scoring scale was recorded at baseline, 14th day and 21st day. Comparing the plaque index for Group A with group B the reduction in from baseline to 14 day was 42.59 % and 38.62% respectively while from baseline to 21 day was 56.20% and 68.57% respectively. On comparing Gingival index for group A with group B the reduction from baseline to 14 day was 31.95% and 38.62 % respectively while from baseline to 21 day was 69.95 % and 68.57% respectively. Halitosis Percentage reduction at 14th day from base line was 33.33% and 38.18%; at 21 day from baseline 66.66% and 72.72% respectively for group A and group B. No statistical significant difference for intergroup comparison was found using paired t test. Intra group analysis using unpaired t test was significant for all the indices at different time intervals. Triphala and Ela decoction is organic, easy to prepare economical and equally effective as compared to chlorhexidine mouthwash.